Development of a Spin Board as a Learning Media for PPKn on the Material of Getting to Know Pancasila in Grade III of SD Muhammadiyah 18 Medan - Fatria Cahya Utami (Journal of Elementary School Education, 2026)
This study aims to develop a spinboard learning media for the topic of Understanding Pancasila for third-grade students of Muhammadiyah 18 Elementary School, Medan, to determine the appropriateness of the media, and to determine the practicality of its use in the learning process. This study uses the Research and Development method. and Development (R&D) with a 4D development model that includes the define, design, and develop stages . The research subjects consisted of 27 third-grade students of Muhammadiyah 18 Elementary School Medan. Data collection techniques were carried out through observation, interviews, validation questionnaires from material experts, media experts, linguists, and teacher and student response questionnaires . The results of the study showed that the developed turntable media obtained a validation percentage of material experts of 80% with a feasible category, a validation percentage of media experts of 97% with a very feasible category, and a validation percentage of linguists of 94% with a very feasible category. The results of the practicality test showed that the teacher's response obtained a percentage of 100% with a very practical category, while the student's response obtained a percentage of 86.91% with a very practical category. Based on these results, it can be concluded that the turntable learning media (spinboard ) on the material Getting to Know Pancasila is feasible and very practical to use as a learning medium. This media is able to help teachers in delivering material and create more active, interesting, and enjoyable learning for students.